I know that I know. But do I know that I do not know? - Polyanskaya, Leona (Frontiers in Psychology, 2023)
Metacognition – the ability of individuals to monitor one’s own cognitive performance and decisions – is often studied empirically based on the retrospective confidence ratings. In experimental research, participants are asked to report how sure they are in their response, or to report how well their performance in high-level cognitive or low-level perceptual tasks is. These retrospective confidence ratings are used as a measure of monitoring effectiveness: larger difference in confidence ratings assigned to correct and incorrect responses reflects better ability to estimate the likelihood of making an error by an experiment participant, or better metacognitive monitoring ability. We discuss this underlying assumption and provide some methodological consideration that might interfere with interpretation of results, depending on what is being asked to evaluate, how the confidence response is elicited, and the overall proportion of different trial types within one experimental session. We conclude that mixing trials on which decision confidence is assigned when positive evidence needs to be evaluated and the trials on which absence of positive evidence needs to be evaluated should be avoided. These considerations might be important when designing experimental work to explore metacognitive efficiency using retrospective confidence ratings.